Correction Factors for the LSDG Free-Air Ionization Chamber for Low and Medium-Energy X-Rays with Monte Carlo Calculations - Kouagou Bangassi, Thierry Narcisse; Samba, Odette Ngano; Raynaert, Nick (British Journal of Healthcare and Medical Research, 2022)
Advances in radiation dosimetry continue to improve the accuracy of calibrating photon and electron beams of radiotherapy. This accuracy in the dose delivery to the patient in radiotherapy depends to a large extent on the absolute dosimetry of the irradiation unit. This necessitates the use of an ionization chamber such as Free air ionization chambers (FAC), calibrated in a recognised Standard Dosimetry Laboratory [1]. FACs are widely used by Primary Standard Dosimetry Labs (PSDL) as primary standard for absolute measurement of air kerma in beam of low and medium energy x-rays. It can accurately measure air kerma of x-ray beams of energy up to about 300kV. The purpose of this investigation, was to determine the correction factors of the Free Air Chamber (FAC) using the Monte Carlo calculations.